Kajian Tingkat Kesesuaian Penggunaan Lahan Terhadap Rencana Tata Ruang Wilayah dalam Upaya Mitigasi Bencana di Kecamatan Baturraden Kabupaten Banyumas - Anisa Ika Marliana; Esti Sarjanti; Sutomo Sutomo (Proceedings Series on Social Sciences & Humanities, 2022)
Land use suitability aims to align land use with the development planned by the government as stated in the Regional Spatial Plan. Baturraden District has an area of 4550.76 Ha. This study aims to determine the level of suitability of land use to RTRW in disaster mitigation efforts in Baturraden District, Banyumas Regency. This research is a descriptive research using field survey methods (field research) and geospatial analysis approaches to conduct spatial analysis of land use suitability to RTRW. The population in this study is in the form of land use forms. The sampling technique for land use forms in this study was to use the total sampling technique. The types of data used in this study are secondary data in the form of Landsat Imagery, RBI Map scale 1:25,000 and Banyumas Regency RTRW Map scale 1:40,000. The data collection used is in the form of field observations, interpretation of satellite images, and documentation. Secondary data processing is carried out by overlaying between the Baturraden District Land Use Map and the Banyumas Regency RTRW Map. Data analysis uses qualitative descriptive to explain the degree of suitability of land use to RTRW. The results of this study show that the level of land use suitability of Baturraden District in 2021 is divided into 2 classifications, namely the appropriate and non-appropriate levels. The area in accordance with the RTRW is 2813.18 Ha (61.81%), while the area is not in accordance with the RTRW which is 1737.57 Ha (38.18%). The value of land use suitability in Baturraden District is in the appropriate category (51-100%). Land use suitability is included in the pre-disaster stage, the level of land use suitability is included in the appropriate classification, it is more effective to realize the resilience of the territory from disasters.